2010
DOI: 10.1002/chem.200902409
|View full text |Cite
|
Sign up to set email alerts
|

Double Friedel–Crafts Acylation Reactions on the Same Ring of a Metallocene: Synthesis of a 2,5‐Diacetylphospharuthenocene

Abstract: The synthetic outcome of the Friedel-Crafts acylation of 1',2',3,3',4,4',5'-heptamethylphospharuthenocene reflects the nature of the acylating agent, with alkanoyl anhydride/trifluoromethanesulfonic acid (TfOH) reagents giving monosubstitution at the phospholyl ring, whereas alkanoyl chloride/AlCl(3) gives 2,5-disubstitution. DFT calculations indicate that this unusual double acylation can be facilitated by the intervention of the phosphorus atom at an early stage in the reaction trajectory, with the acyl grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 128 publications
(165 reference statements)
1
12
0
Order By: Relevance
“…An X‐ray diffraction analysis (Figure 3) confirmed the anticipated configuration of 10 . The long phosphametallocene–acyl distances observed in the structural analysis lie in the normal range for this class of complexes30 and imply low rotation barriers about the ketone group (which have been shown by Klys and Zakrzewski to be of the order of ca. 10 kcalmol –1 );35,36 more linearly disposed conformers are therefore likely to be readily accessible through low‐energy rotations.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…An X‐ray diffraction analysis (Figure 3) confirmed the anticipated configuration of 10 . The long phosphametallocene–acyl distances observed in the structural analysis lie in the normal range for this class of complexes30 and imply low rotation barriers about the ketone group (which have been shown by Klys and Zakrzewski to be of the order of ca. 10 kcalmol –1 );35,36 more linearly disposed conformers are therefore likely to be readily accessible through low‐energy rotations.…”
Section: Resultsmentioning
confidence: 52%
“…The study here is interesting because the interception of a quite strongly bound intermediate 9 sheds some light upon the reaction trajectory for the coordination of phospholide anions to late transition metal centres and also provides a rationale for a near‐perfect diastereoselectivity that is observed during the formation of 10 . Strong literature evidence suggests that the reaction of phospholide anions with late transition metal complexes involves the transient formation of η 1 ‐coordinated phospholides,3033 and this incipient η 1 ‐coordination might reasonably be expected to impose a degree of selectivity upon the reaction trajectory for the incoming metal centre. In situ NMR spectroscopic studies showed that careful treatment of phospholide 8 with two equivalents of [FeCp*(Cl)tmeda] under mild conditions (THF, 25 °C) led to complex intermediate 9 (Figure 2) quantitatively, but isolation proved difficult and single crystals suitable for characterisation could only be obtained in low yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of rac ‐ 1 with [PdCl 2 (1,5‐cod)] in freshly distilled, phosphorus pentoxide‐dried CH 2 Cl 2 gave no discernible reaction over 24 hours at ambient temperature; however, in water‐saturated CH 2 Cl 2 , the robust, air‐stable phosphinite complex rac‐ 4 was obtained instantly. No other species were detectable in solution by 31 P NMR spectroscopy, and some indication of the nature of the hydroxide ion binding was provided by clear and distinct 31 P resonances ( δ = 8.3, –177.8 ppm, 2 J PP = 196 Hz) that confirm non‐fluxionality on the NMR timescale …”
Section: Resultsmentioning
confidence: 90%
“…of the conventional catalyst AlCl3 at room temperature [28] or at ~50 °C [29]. This system has been extended for the use of a limited number of possible acylation positions for metallocenes 47 and 48 [30]. Monosubstitution of an acyl group at the two-position ( [23,24]; to address these limitations, TfOH has been utilized [25].…”
Section: Tfoh Catalytic Activity For Various Acyl Donors and Acyl Accmentioning
confidence: 99%